Prevalence of inducible clindamycin resistance amongst methicillin resistant and sensitive strains of Staphylococcus aureus from a tertiary care hospital, West Bengal, India. - Bose, Soma; Payel Chanda; Chattopadhyay, Saswati; Chaudhuri, Surya Jyati; Mondal, Joy (International Journal of Endorsing Health Science Research, 2024)
Background: Staphylococcus aureus is a prevalent pathogen causing both nosocomial and community-acquired infections worldwide. The emergence of methicillin-resistant Staphylococcus aureus (MRSA) due to the acquisition of mecA and mecC genes poses a significant clinical challenge. The injudicious use of clindamycin for treating MRSA has led to the development of clindamycin resistance. This study aimed to determine the prevalence of inducible clindamycin resistance (iMLSB resistance phenotype) in Staphylococcus aureus isolates, employing the D test according to CLSI guidelines, particularly focusing on erythromycin-resistant strains. Methodology: A total of 147 Staphylococcus aureus isolates were subjected to antibiotic susceptibility testing using the Kirby Bauer disc diffusion method. The D test was employed to identify inducible clindamycin resistance. Results: The study revealed that 34% of isolates exhibited inducible clindamycin resistance, 40% demonstrated constitutive resistance, and the remaining 26% exhibited the MS phenotype. Notably, inducible clindamycin resistance was more prevalent in MRSA (40%) compared to MSSA (22%). Conclusion: The findings underscore the importance of incorporating the D test as a mandatory procedure in standard disc diffusion testing to accurately identify inducible clindamycin resistance. This knowledge is crucial for guiding appropriate antibiotic therapy in the face of increasing resistance patterns.